2004
DOI: 10.1128/jb.186.19.6661-6666.2004
|View full text |Cite
|
Sign up to set email alerts
|

Major Role of NAD-Dependent Lactate Dehydrogenases in Aerobic Lactate Utilization in Lactobacillus plantarum during Early Stationary Phase

Abstract: NAD-independent lactate dehydrogenases are commonly thought to be responsible for lactate utilization during the stationary phase of aerobic growth in Lactobacillus plantarum. To substantiate this view, we constructed single and double knockout mutants for the corresponding genes, loxD and loxL. Lactate-to-acetate conversion was not impaired in these strains, while it was completely blocked in mutants deficient in NADdependent lactate dehydrogenase activities, encoded by the ldhD and ldhL genes. We conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…It has been reported that this gene plays an important role in production of L-lactate during fermentative growth of B. subtilis (14,34). In some other bacteria, similar NAD-dependent L-lactate dehydrogenases were shown to be capable of reversibly interconnecting pyruvate and lactate (23). We therefore wondered whether in B. subtilis, the lctE gene also contributes to L-lactate utilization.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that this gene plays an important role in production of L-lactate during fermentative growth of B. subtilis (14,34). In some other bacteria, similar NAD-dependent L-lactate dehydrogenases were shown to be capable of reversibly interconnecting pyruvate and lactate (23). We therefore wondered whether in B. subtilis, the lctE gene also contributes to L-lactate utilization.…”
Section: Resultsmentioning
confidence: 99%
“…pGIBD001 is a derivative of pGICB002 (14), in which the luxAB genes have been replaced by a chloramphenicol resistance cassette (P32-cat). To obtain plasmid pGIBD001, plasmid pGICB002 was reverse amplified by PCR with primers pJUDdelcomX1 and pJUDdelcomX2, which hybridize upstream and downstream of luxAB, respectively, and then ligated to the P32-cat cassette obtained as a PvuII restriction fragment from pUC18Cm (19).…”
Section: Methodsmentioning
confidence: 99%
“…any bacteria can use lactate as the sole carbon and energy source for growth (9,16,17,22,30). NAD-independent lactate dehydrogenases (iLDHs), which catalyze the oxidation of lactate to pyruvate via a flavin-dependent mechanism, play an essential role in the utilization of lactate in most lactate-utilizing bacteria (8,15,16,17).…”
mentioning
confidence: 99%
“…NAD-independent lactate dehydrogenases (iLDHs), which catalyze the oxidation of lactate to pyruvate via a flavin-dependent mechanism, play an essential role in the utilization of lactate in most lactate-utilizing bacteria (8,15,16,17). iLDHs can be classified into 2 subfamilies (D-iLDH and L-iLDH) depending on their substrate specificities (D-lactate versus L-lactate) (14).…”
mentioning
confidence: 99%